KAJIAN TEORITIS TENTANG UKURAN PERUSAHAAN DAN JUMLAH DEWAN DIREKSI TERHADAP KINERJA KEUANGAN PERUSAHAAN MELALUI PENERAPAN MODEL COSO ENTERPRISE RISK MANAGEMENT - Frisma Novela Arisandy; Siti Maria Wardayati; Yosefa Sayekti; Alfi Arif; Warsito Warsito; Septarina Prita DS; Nining Eka Wahyuni (ITB AAS INDONESIA, 2022)
This study aims to discuss the theory of Firm Size and the number Boards of Directors on the Company Financial Performance through COSO Enterprise Risk Management. This research was conducted to examine the factors that can support the Company Financial Performance. The focus of this research is on COSO ERM using a sampling technique conducted through the Enterprise Risk Management Division. This type of research uses a qualitative descriptive method with a theoretical study of the factors that affect the Company Financial Performance. The results of this study indicate that: 1) Company size plays an important role in supporting the Company Financial Performance. 2) Company size plays an important role in supporting the implementation of COSO ERM. 3) The number of Directors plays an important role in supporting the Company Financial Performance. 4) The number of directors plays an important role in supporting the Company Financial Performance. 5) The implementation of COSO ERM plays an important role in realizing the Company Financial Performance. From the results of the analysis for the next stage of development research, statistical tests will be carried out with SEM analysis.